Prevalence of osteoporosis in hysterectomised as compared to non-hysterectomized women in 7th decade of life - Shamim, Saba; Lal, Manju; Shamim, Rana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Osteoporosis is considered as a major public health issue with fragility fractures of the hip, vertebrae and distal radius being the most important consequences. It has been said to be an age-related degenerative process. However, postmenopausal women develop this disease due to age-related bone mineral loss as well as due to declining levels of estrogen in the body following menopause leading to increased risk of fractures. Objectives of this study were to find out the prevalence of osteoporosis in hysterectomised and non-hysterectomised postmenopausal women in 7th decade of life. Methods: Descriptive cross-sectional study done on a total of 66 postmenopausal women who were in their 7th decade of life. They were divided into two groups, one consisting of 36 women who underwent natural menopause and the other group of 30 women who had surgical menopause. The bone mineral density of both the groups was measured using DEXA scan and comparison was done between these study groups. Results: Out of 30 hysterectomised subjects, 24 (80%) were found to be having osteoporosis, 6 (20%) had osteopenia and none had normal BMD. While out of 36 subjects in the non-hysterectomised group, 14 (38.88%) had osteoporosis, 16 (44.44%) had osteopenia and 6 (16.66%) subjects had normal BMD. Significant relation (p-value 0.001) was found on comparison of the study groups. In addition, significant positive correlation was between BMD and BMI whereas negative correlation was seen between BMD and parity. Conclusions: Hysterectomy was found to increase the incidence of osteoporosis. Obesity was found to have protective effect against bone mineral loss while increasing parity had a negative relation with BMD.